2022
DOI: 10.1186/s13052-022-01393-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the use of antibiotics in pediatric patients hospitalized for varicella

Abstract: Background Varicella is considered a mild and self-limiting disease, but, in some cases, it may complicate and require hospitalization. Antibiotics are not the first line therapy but in some cases are prescribed either for the management of varicella-related complications or as a preventive strategy. Aim of this study is to analyze the rate and the patterns of antibiotics used in pediatric patients hospitalized for varicella as well as the relative costs in order to increase insights in antibio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…For example, in the primary care study in Belgium, 27% of patients with varicella were prescribed antibiotics, with the highest rate in patients with complications (64%) and in those <1 year of age (42%) [ 9 ]. A study of pediatric inpatients at a single hospital in Italy found that 43% of patients with varicella were prescribed antibiotics [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the primary care study in Belgium, 27% of patients with varicella were prescribed antibiotics, with the highest rate in patients with complications (64%) and in those <1 year of age (42%) [ 9 ]. A study of pediatric inpatients at a single hospital in Italy found that 43% of patients with varicella were prescribed antibiotics [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study from Latin America and Europe among children 1–14 years old with varicella reported that 13% of outpatients and 69% of inpatients were prescribed an antibiotic [ 10 ]. More recently, a pediatric study at a hospital in Rome found that 43% of patients admitted for varicella received antibiotics, and a study in primary care in Belgium reported that 27% of patients with varicella were prescribed antibiotics [ 9 , 14 ].…”
mentioning
confidence: 99%